Efektivitas Kinerja Gubernur Ditengah Efisiensi Anggaran (Wacana Penghapusan Jabatan Gubernur) - Jiddan Gamal Qondas; Sutopo Sutopo (Institut Pesantren Sunan Drajat Lamongan, Indonesia, 2023)
The governor is an essential position in the Indonesian constitution. Governors also play an important role in political stability in Indonesia. In Law No. 23 of 2014 concerning Regional Government it is stated in Article 1 paragraph 3 that the Governor / Regional Government is the Head of the Region as an element of regional government administration that leads the implementation of government affairs which are the authority of the autonomous region, it is emphasized again in Article 4 paragraph 1 that the Region Apart from having the status of a Region, the Province is also an Administrative Region which is the working area for the governor as the representative of the central government and the working area for the governor in carrying out general government affairs in the Province Region. As a representative of the central government in the region, the governor is considered a position that is less effective, plus the APBN funds spent to finance his performance are said to be quite large as a representative of the central government. So that this becomes a discourse in the community about the effectiveness of the governorship.